Ellie's long walk : the true story of two friends on the Appalachian Trail - Flowers, Pam.; Farnsworth, Bill (Portland, OR : WestWinds Press, 2012)
Tells the story of the author and her dog Ellie as they hiked from Maine to Georgia on the Appalachian Trail from August 24, 2008 to March 10, 2009.
2.4
K-3
Center for the Collaborative Classroom Curriculum
AD580L
Keywords: Flowers, Pam -- Travel -- Appalachian Trail -- Juvenile literature; Voyages and travels -- Juvenile literature; Hiking -- Appalachian Trail -- Juvenile literature; Dogs -- Juvenile literature; Flowers, Pam -- Travel -- Appalachian Trail; Voyages and travels; Hiking -- Appalachian Trail; Dogs